Pengaruh Media Pembelajan Games Book terhadap Minat Baca Peserta Didik Kelas V di Sekolah Dasar - Siti Nur'ariyani; Ujang Jamaludin (Departement of Mathematics Education, 2022)
The importance of reading skills in developing literacy skills and improving language skills. Reading literacy is also seen as a tool that develops knowledge, skills, and strategies that individuals build throughout life in various contexts. Seeing the reality on the ground today that students' reading interest is low, appropriate strategies are needed to foster students' interest in reading, so that when carrying out reading activities at school and also at home students feel happy and not bored. The solution that can be done is to apply learning using the learning media Games Book. Games Book is a learning media in the form of books in which there are interesting games. Implementation of this research using quantitative methods with a descriptive approach. The population that was used as the object of this study were students at SDN Drangong 1 Serang City and the sample in this study were students in class V at SDN Drangong 1 as many as 26 students. The research instrument used in this study used a non-test in the form of a questionnaire on the attitude scale of students. The attitude scale used in this study is the Likert Model attitude scale. Data from student attitude scales were collected and then analyzed using the a priori method. Based on the results of the research and data analysis that has been done about the influence of game book media on the reading interest of fifth grade students at SDN Drangong 1, it was obtained that the average student questionnaire showed a positive attitude towards learning the game book learning media by 74% while the average participant questionnaire students show a positive attitude towards learning games book learning media by 7%.